2020
DOI: 10.1002/ijfe.1980
|View full text |Cite
|
Sign up to set email alerts
|

Predicting GDP growth with stock and bond markets: Do they contain different information?

Abstract: This paper examines the ability of bond and stock markets to predict subsequent GDP growth over a range of horizons for 12 international countries. The results, using linear, probit, time‐ and regime‐varying in‐sample regressions and out‐of‐sample forecasting, confirm the view that both financial markets exhibit predictive power for future output growth. Moreover, there is notable variation within the strength of the predictive relation, for example, predictive power increases during the financial crisis perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
(73 reference statements)
2
3
0
Order By: Relevance
“…They note that while the bond market is typically preferred to the stock market, overall predictive power is enhanced by including both. A similar result is also reported by McMillan (2021) who argues that the stock market provides greater predictive power during ‘normal’ periods, but the bond market is better at capturing recessionary periods. Both papers link with Chinn and Kucko (2015), who note changing predictability arises from unsettled economic conditions.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…They note that while the bond market is typically preferred to the stock market, overall predictive power is enhanced by including both. A similar result is also reported by McMillan (2021) who argues that the stock market provides greater predictive power during ‘normal’ periods, but the bond market is better at capturing recessionary periods. Both papers link with Chinn and Kucko (2015), who note changing predictability arises from unsettled economic conditions.…”
Section: Introductionsupporting
confidence: 85%
“…For example, Harvey (1989) and Stock and Watson (1990) both argue that term structure provides greater predictive power for subsequent growth compared to the stock return. Kuosmanen and Vataja (2019) and McMillan (2021), while confirming this view also report that improved predictive power is found by incorporating both stock and bond market information. To date, this has not been extended to consider the VRP and default yield (DFY), which may better capture market risk and thus, predictability.…”
Section: Introductionsupporting
confidence: 79%
“…When stocks in a given sector go up, more often than not that sector will show a rise in sales, earnings, and outlays for plant and equipment." McMillan (2021), using quarterly data from 1973 to 2017 for 12 countries, found that stock prices have predictive power for future GDP in several cases. Liu et al (2007), employing monthly data from 1987 to 2004 for many countries, reported that industry valuations implicit in industry earnings data closely follow industry stock prices in several countries.…”
Section: Stock Prices and Finance Theorymentioning
confidence: 99%
“…The macroeconomic literature has established that future real economic growth is positively correlated with lagged interest spreads (e.g., Stock and Watson 1989;Estrella and Hardouvelis 1991;Plosser and Rouwenhorst 1994;McMillan 2021a). In parallel, the link between interest rates and commodities has been also investigated and can be classified into two categories.…”
Section: Literature Reviewmentioning
confidence: 99%